Aplikasi Khusyuk Solat Menerusi Pendekatan Teknik Biofeedback = The Application of Devout (Khusyuk) Prayer Through the Biofeedback Approach - Norsuhaila, Musa; Mohamad Hilmi, Mat Said; Muhammad Nubli, Abdul Wahab (Universiti Sains Islam Malaysia, 2014)
o be recognized as a successful believer of god, engrossed in prayers is the key factor that has a positive impact on the individual’s prayers. Allah says in Surah Al - Mukminun 1-2 verse that: “Successful indeed are the believers, those who humble themselves in their prayers. “Although the concentration is not within the conditions of the pillars of prayer and it does not mean we can belittle it but it is still a claim. There are various ways and methods which are presented as a guide to the implementation of the humble and perfect prayers. But there is no method for measurement that can assess the level of concentration an individual is trying to achieve during prayers. The effectiveness of teaching about prayers can be evaluated through an assessment conducted on each student individually and collectively. The evaluation includes mastery of the three pillars in the prayer. Thus the researcher’s humble opinion is if the elements( what three elements) were incorporated in the existing assessment ,certainly without any doubt students will gain exposure to the performance of more perfect prayers. This study introduces an additional technique for the assessment of prayers. The assessment process undertaken includes the use of an complete inventory conducted on prayers both orally and in practical. The students performance of prayer are also evaluated using biofeedback techniques. Through this technique, the level of psychophysiology students are tracked using the emWave biofeedback equipment. Data is taken during students performing their prayers from the performance Heart Rate variability (HRV). Data acquisition process involves 20 students who are assessed during their prayers. The results showed that the technique is capable of measuring the extent students master their obligatory humble prayers. The study was also able to detect a balance in the HRV spectrum while performing prayers.